Development of a novel fluorescent gauze using indocyanine green - Takeshi Urade; Shinobu Tsuchida; Kentaro Oji; Yoshiaki Fujiwara; Yasushi Fukuoka; Takahiro Yasuda; Takumi Fukumoto (Scientific Reports)
Abstract Gauzes are used in various ways, including wiping blood, compressing organs, and as markers during surgery. However, losing gauze during surgery can lead to pieces being left inside the body, causing time-consuming searches and unnecessary radiation exposure. To address this, we developed a fluorescent gauze using indocyanine green (ICG), which fluoresces under near-infrared (NIR) light. This study aimed to evaluate the fluorescence intensity (FI) of the gauze and confirm its fluorescence in a porcine abdominal cavity. We dissolved 25 mg of ICG in 10 ml of glycerol, ethanol, distilled water, and 5% bovine serum albumin, then diluted each solution 5- to 106-fold with distilled water. The gauze was dyed using these solutions. A rigid laparoscope observed the fluorescent gauze in a dark room under NIR light, and FI was measured. The gauze treated with a 100-fold dilution of each ICG dyestuff showed the strongest fluorescence. This gauze was then placed in a pig’s abdominal cavity and observed under NIR light, demonstrating that the fluorescence could penetrate two or three layers of the mesentery. Our fluorescent gauze, confirmed both ex vivo and in vivo, should be manufactured for clinical use and further validated for its utility.